Impact damage resistance of CFRP prepreg laminates with dispersed CSP particles into ply interfaces - Ali, Mubarak (2013)
The effects of incorporating core shell polymer (CSP) particles within interply interfaces on the impact response of CFRP prepreg laminates are investigated. The impact tests were conducted on samples without and with CSP particles into the ply interfaces. The loads versus time curves were examined to determine the impact response and the associated energy absorption by the laminates were studied. The results indicate that both, the peak load of the laminates improved by 41% and damping index (DI) reduced by 90% with the dispersion of 51 g/m2 of CSP particles within the prepreg ply interfaces of the laminates. It was noted that the CSP particles shielded the composites from the initial severity of impact. The energy absorbing mechanisms altered the supercritical response of the laminate to subcritical due to increase in the elastic energy stored within the laminates with CSP particles thereby changing the energy absorption modes. It was observed from macroscopic observations and SEM images of the damage sites that the damage mechanism and patterns changed and the extent of damage reduced with the addition of CSP particles.